Income Inequality in the Context of Sustainable Development: Interrelations and Empirical Evidence - Sikka, Pooja (2010)
The phenomenon of income inequality has been a source of worldwide economic and social upheaval. Owing to the existence of wide income disparities among countries, all development cannot be termed as sustainable development. It is a widely held view that income inequality and a degraded environment are closely inter-related, especially where people depend for their livelihoods primarily on the natural resource base of their immediate environment. The survival needs of the poor force them to continue to degrade an already degraded environment. Removal of extreme income inequality is therefore a prerequisite for the protection of the environment. The findings of the paper reveal that distribution of income is highly unequal between major advanced economies and countries belonging to developing Asia. Not only is there enormous variation in domestic products across countries but also the composition of domestic products differs across advanced nations and developing nations. Most of the domestic products come from the service sector for each country. However, the service sector is contributing more to the major advanced economies compared to developing Asia. The agriculture sector is contributing little (at the most 2 per cent) in the GDP of major advanced economies. But in developing Asia still a major portion of GDP comes from the agriculture sector. By carrying out cross country regressions, the study finds that the increase (decrease) in the share of agriculture and manufacturing sector result in the decrease (increase) in the overall inequality. On the other hand, the industry and service sector have a positive relation with inequality. It reveals that increase in the share of services and manufacturing sector in developing Asia has resulted in more unequal distribution of income. As the primary goal of sustainable development is to achieve a reasonable and equitably distributed level of economic well-being that can be perpetuated continually for many human generations. Hence, there is strong need of the hour to develop some rules which will guide global redistribution.